Analisis Kesalahan Siswa Dalam Mengerjakan Soal Cerita Materi Segitiga Berdasarkan Teori Polya di SMP Negeri 1 Eris - Nelwan, Andriani Waraney; Manurung, Ontang; Samosir, Rosauli N. (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This research aims to analyze the mistakes made by students in solving story problems about triangle material based on Polya's theory. The type of research applied is qualitative descriptive. Data was collected through written tests and interviews. A total of 33 students from grade VIII participated in this study. From the results of the description test carried out by 33 students, 3 students were selected to be interviewed, representing the high, medium, and low ability categories. The selection of research subjects was carried out by purposive sampling technique. Data condensation, data presentation, and conclusion-drawing techniques are used for data analysis. The findings of the study show that students with high ability can complete all four stages of Polya, students with moderate ability are able to complete three stages, while students with low ability can only complete two stages of Polya.